Interoperability Requirement to Enhance Collaboration in Software Product Lines: A Systematic Mapping - Neiva, Frâncila Weidt; Campos Junior, Heleno de Souza; David, José Maria N.; Braga, Regina Maciel; Araújo, Marco Antônio Pereira; Campos, Fernanda Claudia Alves; Maciel, Rita Suzana Pintangueira (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2016: Anais do XIII Simpósio Brasileiro de Sistemas ColaborativosDO - 10.5753/sbsc.2016.9493, 2016)
[Background]: Software Product Lines (SPLs) have been widely discussed in literature as part of solution to build systems solutions in a collaborative way. Providing interoperability support is an essential requirement to achieve effective results in collaborative systems field. Despite the importance of interoperability in SPLs, research related to this field is scarce and scattered in literature. Fulfilling this requirement is not a trivial task and a mapping study about which interoperability solutions have been tackled in SPLs has not been done yet. [Goal]: This paper aims at identifying and classifying research related to interoperability in SPLs. [Method]: Conduct a systematic mapping to identify and classify SPL interoperability solutions. [Results]: The classifications showed that syntactic was the main addressed interoperability level and that architecture and variability issues were the focus of the SPL researches. [Conclusions]: The results have suggested that an expressive number of solutions related to the syntactic interoperability level were proposed. However, some challenges remain opened, such as providing higher interoperability level support, for example, regarding pragmatic, dynamic and conceptual interoperability solutions.